Factors influencing attitudes of resident communities towards marine resources use in Tun Sakaran Marine Park, Sabah - Mohd Yusah, Habibah; Shuib, Ahmad (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
The coral reef ecosystem provides goods and services that are now more than ever needed by growing coastal population. Despite less than 0.2% of seafloor being covered by reefs, they support 25% of marine fish species in the world. Globally, coral reefs are seen as a dynamic ecosystem subjected to natural and anthropogenic disturbances. In terms of anthropogenically driven causes, major disturbance comes from presence and interaction of human dominance on the ecosystem. Located in the heart of the ‘Coral Triangle’, Semporna’s dynamic mix of ecosystems support flora and fauna including mangroves, seagrass beds and coral reefs. Semporna is well known for its extensive marine biodiversity in particular that of its coral reefs. However, a report states that the current situation in Semporna is critical with only 5% of live coral coverage being in excellent condition. Meanwhile, highlighted issues in the Tun Sakaran Marine Park in the northern side of Semporna waters since now and then was heavy fishing pressures combined with destructive fishing practices which left the resources at an unsustainable condition if it continues. One of the main objectives of the TSMP establishment is to ensure the sustainability of resources use and bring environmental, social and economic benefits to the people. Hence, going deeper, this work attempts to assess the interaction between resident communities and marine resource use after being gazette of more than a decade. A closer look into community socio-economic well-being and place attachment might reveal how different identities could possibly emerging critical issues that influencing individual attitudes towards sustainability marine resource use.